Seed quality differences in diverse seed colored Indian mustard (Brassica juncea) genotypes - Yadav, Sangita; Yadav, Shiv K; Swami, Sunil; Saini, NAVINDER; Hussain, Zakir; Vasudev, Sujata; Yadava, D K (The Indian Journal of Agricultural Sciences, 2020)
‘Canola quality’ Indian mustard (Brassica juncea) with varying seed color are a new kind of breeding resources with single zero genotypes having low level of erucic acid (<2%) while double zero genotypes have both low erucic and glucosinolate content (<30 μmole/g defatted meal). In order to know the variation in seed quality of different types of Indian mustard, in the present study nine genotypes consisting of conventional as well as ‘canola quality’ having either black or yellow seed testa colour were subjected to multivariate analysis including principal component (PCA) and cluster analysis of physiological and biochemical parameters. Data for physiological, biochemical and seed vigour trait was recorded and analysed during 2017–18 at ICAR-Indian Agricultural Research Institute, New Delhi. The first three axes of the PCA captured 85% of the total variation encountered and identified water uptake ratio, electrical conductivity (EC), PUFA/MUFA ratio and Malondialdehyde (MDA) values positively contributing to most of variation while melanin content, total phenol content, germination percentage, vigour indices and glucosinolate content contributed negatively. Cluster analysis classified these genotypes into two distinct groups based on seed testa colour. Black seeded genotypes clustered in group 1 and yellow seeded genotypes clustered in groups II. Moreover, these techniques also differentiated canola from conventional genotypes among their testa groups. The majority of yellow-seeded genotypes had low melanin and total phenol content in testa causing rapid water uptake and higher leakage than the black-seeded genotypes, which led to imbibition damage resulting in lower germination percentage and seed vigour indices.